2020
DOI: 10.3390/inventions5040061
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time LFO Damping Enhancement in Electric Networks Employing PSO Optimized ANFIS

Abstract: In recent years, machine learning (ML) tools have gained tremendous momentum and received wide-spread attention in different segments of modern-day life. As part of digital transformation, the power system industry is one of the pioneers in adopting such attractive and efficient tools for various applications. Apparently, a nonthreatening, but slow-burning issue of the electric power systems is the low-frequency oscillations (LFO), which, if not dealt with appropriately and on time, could result in complete ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, damping controller design is an optimization-centered process that requires the exploitation of various optimization algorithms [32]. The damping of power system oscillations with damping controllers mostly depends on the tuning strategy adopted in obtaining the optimal parameters [33]. Time integral performance criteria for calculating the integral error of the damping controller [32] and the eigenvalue-based stability analysis on the multi-machine test system are employed to evaluate the performance of damping controllers.…”
Section: Offshore Platformmentioning
confidence: 99%
“…However, damping controller design is an optimization-centered process that requires the exploitation of various optimization algorithms [32]. The damping of power system oscillations with damping controllers mostly depends on the tuning strategy adopted in obtaining the optimal parameters [33]. Time integral performance criteria for calculating the integral error of the damping controller [32] and the eigenvalue-based stability analysis on the multi-machine test system are employed to evaluate the performance of damping controllers.…”
Section: Offshore Platformmentioning
confidence: 99%
“…Moreover, FLC struggle when dealing with highly complex and nonlinear systems, which can be a limitation when trying to control the dynamic behaviour of power systems with UPFC. The newly generated real-time dynamics were controlled using an intelligent control approach, specifically the adaptive neuro fuzzy inference system (ANFIS) technique [37]. ANFIS models lack transparency, making it difficult to understand the reasoning behind control decisions, which can be a concern for critical systems like UPFC.…”
Section: Introductionmentioning
confidence: 99%
“…NN controller was used to replace PSSs and AVR on a SMIB test power system for control of LFOs (Abdulgabbar and Ahmed, 2017). ANFIS controllers-based PSO have been implemented for real-time LFO damping improvement in Pathan et al (2020), where the ANFIS controllers were found to be able to sustain the dynamic stability of the multi-machine test systems successfully. Type-2 fuzzy PID-PSSs (Shokouhandeh and Jazaeri, 2018) was developed to improve the stability of multi-machine power systems.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, input MF of the T2FLS is three Gaussian MFs. The authors in Pathan et al (2020) studied the role of a prominent machine learning family member, PSO to optimized ANFIS for real-time improvement of LFOs on SMIB test system. These AIs structures and configurations are usually not model-free designed; as such, these will cause a very high computational cost for operating the controller on a large scale test power system.…”
Section: Introductionmentioning
confidence: 99%